A systematic review on the health effects of fermented wheat germ extract with emphasis on cancer - Berkel Kasikci, Muzeyyen; Issa, Aline; Baglam, Nurcan; Dincer, Emine; Gérard, Amaury; Kabakci, Sumeyye; Özyurt, Vasfiye Hazal; Zalán, Zsolt; Şar, Taner; Gündüz Ergün, Burcu; Chassard, Christophe; Praćer, Smilja; et al. (Frontiers in Nutrition, 2025)
Fermented wheat germ extract (FWGE) is one of the few fermented food products listed in the EFSA novel food Catalogue. It is derived from wheat germ, a by-product of wheat processing, through fermentation with Sacchoromyces cerevisiae. The most widely studied and patented form of FWGE is marketed as Avemar (also referred to as MSC), standardized to contain methoxy-substituted benzoquinones. Given its predominant use in research, this systematic narrative review focused primarily on FWGE use within the medical application. The objective of this review was to systematically evaluate the functionality and potential health benefits of FWGE, following the Study Protocol-S8 developed under COST Action CA20128 – PIMENTO and registered on the Open Science Framework (https://osf.io/fq53j/). A systematic literature search of human studies was conducted through PubMed, Scopus, and Cochrane Library. Studies involving adult participants who received FWGE interventions were included, with primary clinical endpoints selected according to the main indications for FWGE. Additional outcomes were reported when available. Out of the 51 records identified by the literature search, six studies met the inclusion criteria. Data from these studies were extracted and synthesized in summary tables. Supplementary information on the functionality of FWGE was retrieved through a non-systematic search of animal and in vitro studies. Furthermore, this review highlights the potential bioactive constituents of FWGE, particularly benzoquinones, peptides, and phenolic compounds, as mediators of its anticancer and anti-inflammatory properties. Among its proposed mechanisms, FWGE may suppress cancer cell proliferation by disrupting the glucose-related metabolic pathways. While the findings suggest that FWGE may possess therapeutic potential, especially in oncology, the strength of evidence remains limited. Of the six included human studies, only four employed proper control groups and only two demonstrated high methodological quality. As such, the current evidence base is insufficient to draw definitive conclusions, and well-designed clinical trials are needed to strengthen this evidence. Moreover, future research should also explore the development of novel FWGE formulations with enhanced bioactive profiles, optimized by modulating fermentation conditions, including such as microbial strain, pH, temperature, and duration.